The impact of attraction for environmental graphic design on Cherating surf camp / Munirah Othman - Othman, Munirah (2015)
Environmental design is the process of addressing surrounding environmental parameters when devising plans, programs, policies, buildings, or products. Environmental design can also refer to the applied arts and sciences dealing with creating the human-designed environment. These fields include architecture, geography, urban planning, landscape architecture, interior design and graphic design. Environmental design can also encompass interdisciplinary areas such as historical preservation and lighting design. In terms of a larger scope, environmental design has implications for the industrial design of products: innovative automobiles, wind-electricity generators, solar-electric equipment, and other kinds of equipment could serve as examples. Currently, the term has expanded to apply to ecological and sustainability issues. The purpose of this research is to analyze the impact of interaction environmental design and branding identity on surf camp Malaysia. To understand environmental design, it is important to know the area itself and the culture. This research will focus on local people from age 21 until 35 years old. Surfing has long been of interest to local people but is not given exposure because of this sport in monsoon season. The environment also gives a big role to attract people to join in surf camp. One research question has been formulated in order to get an answer posed in this research. This can be measured and testable data which involves both qualitative and quantitative research to gather and analyze implicit and explicit about environmental design in Cherating surf camp, Malaysia. In order to get the result to support and solve the problem, a primary such as questionnaire has to be hand around and interviewed to the target audience and also secondary data such as site visit for visual, article and journal. The results will 100% based on the interview, questionnaire and research to get the solution of the problem. The questionnaire objective is to know what local people in Malaysia attract to and what kind of service will be easier to they understand. The way to bring attraction is to come out with new idea in environmental design at the surf camp and create a new branding identity for Malaysia surf camp. The environmental design will be choose one concept of Malaysia identity like the camp layout which is environmental design, landscape and interior design. The surf camp Malaysia logo identity also has to create a new one that locals can be remembers. However, include promotion to support the environmental design and branding identity. Promotion that will imply visual and strong promotion such as poster, brochure, postcard and alternative media social to attract more locals to join the surf camp.